An Introduction to Veterinary Medicine Engineering - Bressan, Nadja; Creighton, Catherine M. (Cham : Springer International Publishing : Imprint: Springer, 2023)
Do cephalopods change color when under distress? Is the reptilian heart analogous to a diaphragm positive displacement pump? Are digital twins the answer for animal experimentation? This book explores the new field of veterinary engineering science and discusses how to better measure vital signs in exotic and companion animals. A vast opportunity exists for developing novel technologies that target reductions to the number of invasive procedures patients are subjected to. We examine improvements to animal care and enhancement of animal welfare while creating a more sustainable veterinary healthcare ecosystem. The authors address the challenges engineers face in designing healthcare equipment for animals and how the field of veterinary engineering contributes to traditional veterinary medicine. This book brings a novel field of engineering to train future veterinarians and engineers on design and application of technology to veterinary medicine.
Keywords: Regenerative medicine; Veterinary medicine; Animal biotechnology; Biomedical engineering; Biotechnology; Regenerative Medicine and Tissue Engineering; Veterinary Science; Animal Biotechnology; Biomedical Engineering and Bioengineering; Biotechnology